The Possibility of Applying the Tools of Lean Manufacturing: A Field Study in Mosul Dairy Factory - Moatasem H. M. Salih (Journal of Techniques)
This research tries to define the concept of the lean manufacturing and its tools. Also is aiming to determine the possibility of applying the tools of the lean manufacturing system in  Mosul Dairy Factory. The research is choosing the Mosul Dairy Factory as  a study field to support the nation products in the country. It is important for other factories to look at the benefits of this system and apply it to avoid the wasting in the manufacturing and use the available energy. This will help the factories to compete with the imported products from aspects، which are the production cost and the quality. The assumption of the research has been tested by using the ways of the statistics and by using (SPSS). Also، it is been employed filed survey as a main tool to gather data and information from the study sample. Researcher reached a number of conclusions، the most important of which was the availability of the tools of the lean manufacturing in the Mosul Dairy Factory. All the lean manufacturing tools is varying، which means there is a way to apply them in the study sample. Based on the conclusions of the research many recommendations have been submitted to Mosul Dairy Factory.